Semiconductive Nanotube Array Constructed from Giant [PbII18I54(I2)9] Wheel Clusters - Wang, Guan-E; Xu, Gang; Liu, Bin-Wen; Wang, Ming-Sheng; Yao, Ming-Shui; Guo, Guo-Cong (Angewandte Chemie International Edition, 2016)
Crystalline nanotube array would create great opportunity for novel electrical application. Herein we report the first example of a metal halide based crystalline nanotube array which is constructed from an unprecedented giant [PbII18I54(I2)9] wheel cluster, as determined by synchrotron X‐ray diffraction. The electrical properties of the single crystal were studied and the present compound shows typical semiconductivity and highly anisotropic conductivity. Lead the way to the tube: The first example of a metal‐halide‐based crystalline nanotube array is constructed from an unprecedented giant [PbII18I54(I2)9] wheel cluster (see picture, Pb green, I pink). It has typical semiconductive properties and highly anisotropic conductivity.